Naskah Shahadat Sekarat: Konstruksi Nalar Sufistik atas Kematian dan Eskatologi Islam di Jawa - Ibnu Fikri (Manuskripta, 2015)
This article discusses the manuscript of Shahadat Sekarat that was found in the Sukomulyo village at South Kaliwungu, Kendal, Central Java. This article expresses on the mystery of death and Islamic eschatology based on Javanese culture. In addition to describing shahadat of death, Shahadat Sekarat also was writing on the human being concept, the tauhid concept in Sufism context, and some prayer indicated to Martabat Tujuh conception. The death and eschatology terms which are included in this manuscript are the part of Sufism theory that need special inpretation to understand it. Therefore, this article applies the philology and hermeneutics as methodology. This article concluded that Shahadat Sekarat is the doctrine towards the perfection for Islamic Sufism agents in Java. The spiritual conception in Shahadat Sekarat has close of a relationship with the structured Javanese society during this manuscript was written. --- Artikel ini membahas naskah Shahadat Sekarat yang ditemukan di Desa Sukomulyo, Kalingwungu Selatan, Kendal, Jawa Tengah. Tulisan ini mengungkap misteri kematian dan eskatologi Islam dalam bingkai khazanah Jawa. Selain menguraikan tentang shahadat kematian, naskah Shahadat Sekarat ini membahas konsep kejadian manusia, konsep tauhid yang dikemas dalam doktrin tasawuf, serta do’a-do’a yang mengarah pada konstruksi martabat tujuh. Topik kematian dan eskatologi yang terdapat dalam naskah ini merupakan bagian dari materi tasawuf yang membutuhkan interpretasi khusus untuk memahaminya. Berkaitan dengan itu, artikel ini menggunakan kajian filologis dan pendekatan hermeunetik sebagai metodologi. Artikel ini menyimpulkan bahwa Shahadat Sekarat merupakan ajaran untuk menuju kesempurnaan diri bagi pelaku ajaran Islam Sufistik di Tanah Jawa. Konsepsi spiritual yang tertuang dalam naskah Shahadat Sekarat ini memiliki kaitan erat dengan fenomena yang terstuktur dalam masyarakat Jawa pada saat naskah ini dibuat.